Effectiveness of the Mechanisms for Transferring Inherited Land to Heirs Who Are Foreign Nationals - Rahmawan, Evita Nuraini; Djaja, Benny (Jurnal Ilmu Hukum Kyadiren, 2026)
Ownership and the transfer of freehold land to heirs who are foreign nationals constitute a critical issue in Indonesian agrarian law, as they intersect with the principle of nationality, limitations on property rights, and the pluralism of inheritance law. This study aims to provide a comprehensive examination of the normative foundations of the Basic Agrarian Law (UUPA), the regulation of ownership rights, and the mechanisms for transferring or converting the status of inherited land received by foreign national heirs. The research employs a normative legal method using statutory, conceptual, and comparative approaches to analyze relevant legal regulations and doctrines. The findings show that foreign national heirs may inherit freehold land but are required to transfer it within one year through sale, donation, APHW/APHB, or by converting the land status to a right of use. The study concludes that the Indonesian legal framework offers legal certainty while safeguarding national interests, although its implementation still requires strengthening through public outreach and improved administrative mechanisms.